Amelioration of limited mouth opening after treatment of primary biliary cholangitis: A case report. Issue 5 (September 2019) - Kaneuji, Takeshi; Yoshiga, Daigo; Ariyoshi, Wataru; Nakamichi, Ikuo; Tanimoto, Hironori; Tanaka, Junpei; Miyamoto, Ikuya; Habu, Manabu; Mitsugi, Sho; Nishihara, Tatsuji; Takahashi, Tetsu; Tominaga, Kazuhiro; et al.
Abstract: Primary biliary cholangitis is a slow-progressing autoimmune disease of the liver characterized by the presence of portal inflammation and immune-mediated destruction of the intrahepatic bile ducts. Herein, we report a case of temporomandibular joint disorder that concurred with primary biliary cholangitis. A 54-year-old woman presented to us with severe pain on the left side of the temporomandibular joint and difficulty in mouth opening. We used pharmacotherapy, occlusal sprint, and arthrocentesis for the treatment; however, there was no improvement. Magnetic resonance imaging revealed malposition of the articular disk on the left side of the joint and joint effusion. Thus, we performed arthroscopic surgery under general anesthesia. Postoperatively, she developed impaired liver function and itchiness of the skin. A liver biopsy was performed by a hepatologist, and a diagnosis of primary biliary cholangitis was made, as suspected. The temporomandibular joint pain and trismus persisted postoperatively; however, these symptoms improved after primary biliary cholangitis therapy. Thus, we suggest a relationship between temporomandibular joint disorder and primary biliary cholangitis from this disease trajectory and suspect that interleukin-17 may play an important role in the pathogenesis of temporomandibular joint disorder.